TWO NEW SPECIES OF Apostolepis Cope, 1862 (SERPENTES: ELAPOMORPHINI) FROM BREJOS DE ALTITUDE IN NORTHEASTERN BRAZIL - Borges-Nojosa, Diva Maria; Lima, Daniel Cassiano; Bezerra, Castiele Holanda; Harris, David James (Revista Nordestina de Zoologia, 2016)
Two new species of snakes are described of the genus Apostolepis Cope, 1862, that is endemic to Cisandean South America. The new species occur in three areas in the State of Ceará, northeastern Brazil, the “brejos-de-altitude”. Apostolepis mariae sp. nov. occurs in the Serra de Maranguape and Maciço de Baturité, and differs from the others of the genus by the following characteristics: 200-255 ventral scales and 23-36 pairs of subcaudals, dorsal and lateral coloration of head dark brown, light nucal collar completely or partially split (wide 2-3 rows of scales), posterior cervical dark collar (1-2 scales wide), presence of a light spot below the eye (third and fourth supralabials), dorsal and lateral body color reddish brown, with five longitudinal dark brown stripes, persistent in adults, 6 supralabials (fourth and fifth linked to parietal) and 6-7 infralabials (first - fourth linked to anterior chinshields), nasal in contact with preocular, tip of the tail covered by a black band on the dorsal surface and immaculate ventral face or with small spots, and divided anal scales. Apostolepis thalesdelemai sp. nov occurs in the Planalto da Ibiapaba, is very similar to the previous species, but differs mainly by the following characteristics: 212-244 ventral scales and 29-38 pairs of subcaudals, absence of the light nuchal collar (replaced by a spot or light band small), discreet dark cervical collar with ½ - 2 scales of width, partially fused to the dark color of the head, two lateral patches on the head: the first occupying the third and fourth supralabials and the second on the sixth supralabial, five longitudinal dorsal dark brown stripes, a darker vertebral more dark than two pairs of paravertebrals and first pair lighter, and tip of the tail with a dark band on the dorsal and ventral faces. Both are more similar to Apostolepis longicaudata, A. nigrolineata and A. pymi.